Redefining existing functionality of the regulatory portal for immediate access to outputs of employees - Coronel, Aira Juana M.; Talisayon, Serafin (Quezon City University of the Philippines Diliman, Technology Management Center, 2013)
The employees' knowledge is considered as one of the most important sources of a business's competitive advantage. In this regard, companies are beginning to execute plans and implementing methods of keeping said knowledge.
One of the most used methods of recording knowledge is through documents. However, it is not enough for knowledge to be captured; it should be used by those who require it when they need it. In this regard, it is also important for organizations to create a facility that would facilitate the transfer of knowledge from said documents. The most common tool that companies are currently using is an enterprise information portal (EIP).
In recognition of capturing said knowledge and the importance of transferring it to those who require it, there is a requirement to redefine the existing functionality of the Regulatory Management Office (RMO's) Regulatory Portal to address the concern on how to retain and immediately access the knowledge of employees.
In view of the foregoing, it is proposed that a new module shall be incorporated in the existing portal that will introduce an innovative functionality that would be the management of accessing employee's work.
The proposed creation of a new module, which shall be called "Your Work", in the existing Regulatory Portal is aimed at providing the organization a shared database that would allow the employees to store their work in a systematic and organized manner. Further, it will aid the organization to easily retrieve and trace the history of the employee's output. Said module shall also be made centrally available and accessible, not only to the employee but also to the employee's team.
Thesis
Keywords: Human information processing